Hate speech frontiers: exploring the limits of the ordinary and legal concepts - Brown, Alexander (Cambridge University Press, 2024)
"This investigation of the ordinary and legal concepts of hate speech contrasts social media platform content policies with national and international laws. It clarifies how controversial grey areas, such as reverse hate speech, misgendering, gender denialism, blackface or identity appropriation, and righteous hate speech, should be approached"-- Provided by publisher